Prenatal Gentle Yoga untuk Mempersiapkan Persalinan yang Lancar, Nyaman, dan Minim Trauma di Puskesmas Jetak - Feni Noviyani; Yulia Nur Khayati; Aninda Nur Sinto Putri; Rina Pratiwi (Prosiding Seminar Nasional dan CFP Kebidanan Universitas Ngudi Waluyo, 2022)
Pregnancy is a physiological phenomenon that begins with fertilization and ends with childbirth (Patriasari, 2009). According to Nurdiana (2012), the anxiety experienced by pregnant women is caused by the increase in the hormone progesterone. In addition to making pregnant women feel anxious, the increase in hormones also causes emotional disturbances and makes pregnant women tired quickly. Sports that are recommended for pregnant women to maintain the health of the body and fetus so that they develop properly and also make the mother's emotions remain stable are walking, cycling, swimming, pregnancy exercise, hypnobrithing and yoga (Boscaglla, et al., 2003; Bessinger, et al., 2002; Pivarnik, 2008; Larasati and Komolohadi, 2010; Barakat, et al., 2011; Shivakumar, et al., 2011). The purpose of this study was Prenatal Gentle Yoga to prepare for a smooth, comfortable, and minimally traumatized delivery at the Jetak Health Center in 2022. The results of the pre-test of mothers before being given counseling on pregnant yoga were still lacking in knowledge with a total of 10 respondents, 5 of whom lacked knowledge (50%). and 5 of them had good knowledge (50%), and after counseling about prenatal yoga the number of respondents who experienced an increase in knowledge was to be 100%, this indicates that there was an increase in knowledge of 50%. AbstrakMenurut Nurdiana (2012), rasa cemas yang dialami oleh ibu hamil itu disebabkan karena meningkatnya hormon progesteron. Selain membuat ibu hamil merasa cemas, peningkatan hormon itu juga menyebabkan gangguan perasaan dan membuat ibu hamil cepat lelah. Olahraga yang dianjurkan pada ibu hamil untuk menjaga kesehatan tubuh dan janin agar berkembang dengan baik dan juga membuat emosi ibu tetap stabil adalah jalan kaki, bersepeda, berenang, senam hamil, hipnobrithing dan yoga (Boscaglla, dkk., 2003; Bessinger, dkk., 2002; Pivarnik, 2008; Larasati dan Komolohadi, 2010; Barakat, dkk., 2011; Shivakumar, dkk., 2011). Tujuan penelitian ini adalah Prenatal Gentle Yoga Untuk Mempersiapkan Persalinan Yang Lancar, Nyaman, Dan Minim Trauma Di Puskesmas Jetak pada tahun 2022. Hasil pre tes ibu sebelum diberikan penyuluhan yoga hamil pengetahuannya masih kurang dengan jumlah 10 responden , 5 diantaranya pengetahuannya kurang (50%) dan 5 diantaranya pengetahuannya baik (50%), dan setelah dilakukannya penyuluhan tentang prenatal yoga jumlah responden yang mengalami peningkatan pengetahuan yaitu menjadi 100%, hal ini menunjukkan bahwa ada peningkatan pengetahuan sebanyak 50% .